METHODOLOGY OF ORGANIZING CHEMISTRY LESSONS THROUGH DESIGN (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article presents a methodology for organizing chemistry lessons in a school chemistry course through design. It provides methodological recommendations for increasing students' interest in chemistry, conducting chemistry lessons in a meaningful, understandable, and concrete way with real-life examples. Also; the article studies the stages of forming students' thinking about chemistry through the methodology of conducting experiments with students, understanding the experiments that allow them to perform them in a room.